THE DOMINANCE OF LOTS IN SUMMATIVE ASSESSMENT: THE CHALLENGE OF IMPROVING HOTS IN INDONESIAN LANGUAGE LEARNING - Setyorini, Ririn (EDUCATIONE, 2025)
The competence of teachers in making test questions for students is very diverse. There are teachers who are able to make HOTS questions, there are teachers who are still using HOTS questions. HOTS questions are questions that measure students' level of critical thinking, for that we need to know how the teacher's competence in making HOTS questions so that students can measure their level of critical thinking in mastering the material taught. This study aims to describe the level of LOTS and HOTS questions made by teachers on formative and summative questions in Indonesian subjects.  The participants in this study are junior high school Indonesian teachers in the Brebes area, Indonesia. This type of research is qualitative descriptive. The data and data source are Indonesian teachers in the Brebes area, Indonesia. The results of the study revealed the dominance of LOTS-based questions (Lower Order Thinking Skills) in summative assessment, which covered 66.9% of the total questions, while HOTS-based questions (Higher Order Thinking Skills) only reached 33.1%. This inequality suggests that assessments still focus on basic abilities such as remembering and comprehension, with minimal attention paid to the development of students' analytical, evaluative, and creative skills. This condition reflects the challenges faced in the preparation of questions, such as the lack of technical training for teachers and the limited guidelines for the preparation of HOTS-based questions. These findings have important implications that ongoing training is needed for teachers to improve their ability to design assessment instruments that encourage students to think more deeply and critically.